Mobile game for student standard six to learn Malay proverb using game-based learning theory / Nur Syazana Ramli - Ramli, Nur Syazana (2020)
Mobile devices have become important part in people's life including children as they grown up with digital technologies. Edutainment is a form of entertainment designed to educate as entertain and games is one of the mediums of edutainment. There are a lot of educational game that can be found in market including Malay proverb. The use of Malay proverb is very important in the promotion of Malay as national language so Ministry of Education take steps incorporate proverb in the syllabus. However, students find it difficult to understand the meaning of proverb as it has implicit meaning and it is using figurative language. The objectives of this project are to identify the level of proverb for student standard six, develop mobile game to learn Malay proverb and evaluate user acceptance towards the use of mobile game to learn Malay proverb. The project has been successfully developed by using Waterfall Methodology. The efficiency of this mobile game is demonstrated by conducting a usability test with 20 students of Sekolah Kebangsaan Seri Gedong. Results show that student like use the application as an additional learning material.